High seroprevalence and age-associated dynamics of bluetongue and epizootic hemorrhagic disease viruses in North American bison (Bison bison) - Krus, Catherine; Zander, Ian; Sherman, Tyler J.; Maichak, Courtney; Buttke, Danielle E.; Jones, Lee; Mayo, Christie (Frontiers in Veterinary Science, 2025)
Bluetongue virus (BTV) and epizootic hemorrhagic disease virus (EHDV) are two viruses belonging to the genus Orbivirus that are transmitted via insect vector, the Culicoides biting midge, causing disease in domestic and wild ruminants. These infections can lead to significant morbidity, mortality, and production losses in livestock, with economic consequences for cattle and sheep industries. Despite their growing impact due to environmental and anthropogenic changes, little is known of the prevalence of these viruses in North American bison (Bison bison). We present the first cross-sectional survey of BTV and EHDV in North American bison, with samples collected from 287 animals across 9 herds in 7 U.S. states from September to November 2023. Using competitive enzyme-linked immunosorbent assays (cELISA), we detected seroprevalence rates of 56.5% for BTV and 57.5% for EHDV. We found higher seroprevalence in North American bison compared to reports in European bison populations, suggesting that bison could potentially serve as incidental hosts of orbiviruses during key transmission periods; however, their role in virus transmission remains uncertain and warrants further investigation, particularly regarding the duration of viremia, potential amplification capacity, and year-to-year variability in PCR positivity. Logistic regression analysis revealed age as a significant predictor for both BTV (OR: 1.15, CI: 1.05–1.26, p: 0.006) and EHDV (OR: 1.16, CI: 1.06–1.28, p: 0.0014) seropositivity. PCR amplification identified circulating BTV serotypes 6, 11, 13, 17. Additionally, age was negatively associated with PCR positivity for both BTV (OR: 0.70, CI: 0.53–0.93, p: 0.014) and EHDV (OR: 0.56, CI: 0.33–0.93, p: 0.024), suggesting a decline in detectable viremia with increasing age. Although complex environmental and epidemiological factors likely play a role, this trend may be due to older animals having experienced more vector seasons, thereby increasing their cumulative exposure and subsequent immunity to these viruses over time. The significant age-associated dynamics reveal the importance of considering life stage in disease surveillance and management. Our study also highlights the importance of integrating bison into future vector-borne disease research and control strategies to mitigate risks to livestock, wildlife, and ecosystem health.